Midwifery Care Continuity of Care at Delta Mutiara Clinic and Maternity Hospital, Sidoarjo: Asuhan Kebidanan Continuity Of Care Di Klinik Dan Rb Delta Mutiara Sidoarjo - Nufus, Hayatun; Rosyidah, Rafhani (Jurnal Kebidanan Midwiferia, 2024)
Continuity of Care is a program to improve the provision of midwifery services continuously carried out by Midwives and as the final project for midwifery students by promoting holistic and integrated midwifery care. The aim of this study was to provide continuous midwifery care , 25 year old, Mrs. A at the Delta Mutiara Clinic, Sidoarjo. The research design is descriptive with the case type of study research. The results showed that the midwifery care provided to Mrs. A, starting from pregnancy, childbirth, postpartum, newborns, and family planning, went according to midwifery care standards. Conclusions after being given Continuity of Care midwifery care, the mother feels comfortable, the occurring complications can be resolved and detected since the beginning of pregnancy, the mother and baby received adequate and integrated care.